2018
DOI: 10.1098/rsos.181101
|View full text |Cite
|
Sign up to set email alerts
|

Pressure generated at the instant of impact between a liquid droplet and solid surface

Abstract: The prime objective of this study is to answer the question: How large is the pressure developed at the instant of a spherical liquid droplet impact on a solid surface? Engel first proposed that the maximum pressure rise generated by a spherical liquid droplet impact on a solid surface is different from the one-dimensional water-hammer pressure by a spherical shape factor (Engel 1955 J. Res. Natl Bur. Stand. 55(5), 281–298). Many researchers have since proposed various factors to accurately predict the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Here, ρg is the specific weight, t s . is the droplet spreading thickness, F γ is the surface tension force, ∆V is the volume of inflection, P e f f = 1.41ρc 0 v i − p a is effective impact pressure onset of impact, p a is the maximum pressure in the entrapped air and c 0 is the speed of sound [29].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Here, ρg is the specific weight, t s . is the droplet spreading thickness, F γ is the surface tension force, ∆V is the volume of inflection, P e f f = 1.41ρc 0 v i − p a is effective impact pressure onset of impact, p a is the maximum pressure in the entrapped air and c 0 is the speed of sound [29].…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The maximum pressure is normalized by that in the dry wall (p max (0) = 22 MPa). According to the work by Tatekura et al (2018), calculation of the water-hammer peak pressure that appears at the point contact of spherical droplet impact requires extremely high spatial/temporal resolutions. 67 In this study, we do not intend to resolve the water-hammer event with finer computational grids;…”
Section: A Acoustic Stage Of the Impact Dynamics: Water-hammer Shockmentioning
confidence: 99%
“…As shown in Figure 1, the impact of a free waterjet on soft tissue is divided into the following stages: at t = 0, the highspeed waterjet tip contacts the soft tissue surface; from t to t 1 , the shock wave is formed at the contact point and propagates in the water and soft tissue at different speeds, the pressurized water medium is densely populated in the waterjet tip, and the soft tissue is elastically deformed; from t 1 to t 2 , the waterjet stream continues to impact the soft tissue surface to form a new shock wave, because the velocity of the shock wave is much higher than the velocity of the waterjet, the water hammer pressure generated by the impact at its centre is disturbed by the shock wave until the waterjet tip is in complete contact with soft tissue; at t > t 3 the waterjet impact will form a stable Bernoulli stagnation pressure from the dynamic pressure of the waterjet, and the waterjet centre-pressure is significantly reduced. Experimental studies have shown that the water hammer pressure has a short duration of action, on the order of nanoseconds [14], [15].…”
Section: Waterjet Impact a Water Hammermentioning
confidence: 99%